Feminist Thought and Guidelines for Ethical Psychological Practice With Self-Identifying Women and Girls - Beks, Tiffany A.; Kassan, Anusha; Dyrda, April J.; Elleker, Daniel (Canadian Journal of Counselling and Psychotherapy, 2022)
Several iterations of guidelines for ethical psychological practice with those who self-identify as women and girls have been developed in the field of Canadian psychology and are designed to offer practitioners direction concerning their ethical responsibilities and competencies. But to be responsive to the varied and changing experiences of women and girls within the Canadian context, these guidelines require regular revision. This article discusses avenues for evolving inclusive counselling and psychotherapy practice with women and girls in Canada. While the primary focus is on implications for counselling and psychotherapy practice, the need for ethical texts and guidelines to reflect gender diversity is underscored. Drawing from literature on feminist thought and its applications, this article offers recommendations for ethical and socially just counselling and psychotherapy practice. Additionally, this article is intended to reignite conversation about how future iterations of ethical guidelines may evolve to be more responsive to the current status of those who self-identify as women and girls.